Toxicity effects of water extracts of Holothuria atra Jaeger in mice - Hashim, Ridzwan; Zamli, Zaitunnatakhin; Daud, Jamaluddin (Asian Pacific Journal of Tropical Biomedicine, 2014)
To determine lethal median dose (LD50) and histopathological toxicity of water extract of Holothuria atra (H. atra) in mice. Methods: The behavioral changes, mortality and histopathology examination on liver were assessed in mice 14 d after the administration (i.p.) of H. atra water extract. Seven doses (10, 20, 30, 50, 100, 150 and 200 mg/kg) of H. atra were used. The control group was treated with normal saline. Results: In the acute study in mice, the water extracts of H. atra caused dose-dependent general behavior adverse affects and mortality. The main behavioral sign of toxicity was hypoactivity, noticed immediately after administration of the extract which was more obvious at the higher doses and persisted until death. Mortality increased with increasing doses, the calculated LD50 was 41 mg/kg in mice. The liver toxicity was confirmed by histopathological examination, which indicated the presence of abnormal hepatocytes with a distorted shape and undefined cell lining as well as enlarged nuclei in low doses groups. High doses groups indicated a more prominent distortion of the polyhedral hepatocytes with undefined cell lining, massive cytoplasm, pyknotic, karyorhexis and karyolytic nuclei (necrosis of hepatocytes). Control group showed polyhedral hepatocytes with defined cell lining arranged in cords and normal round nuclei, with granular cytoplasm. Conclusions: Because of the relatively low LD50 value in the acute study in mice, it may be concluded that the H. atra water extract is toxic.